Metabolic Mechanisms Underlying Heat and Drought Tolerance in Lentil Accessions: Implications for Stress Tolerance Breeding - El Haddad, Noureddine; En-nahli, Youness; Choukri, Hasnae; Aloui, Khawla; Mentag, Rachid; El-Baouchi, Adil; Hejjaoui, Kamal; Rajendran, Karthika; Smouni, Abdelaziz; Maalouf, Fouad; Agrawal, Shiv Kumar (MDPI, 2023)
Climate change has significantly exacerbated the effects of abiotic stresses, particularly high temperatures and drought stresses. This study aims to uncover the mechanisms underlying heat and drought tolerance in lentil accessions. To achieve this objective, twelve accessions were subjected to high-temperature stress (32/20 °C), while seven accessions underwent assessment under drought stress conditions (50% of field capacity) during the reproductive stage. Our findings revealed a significant increase in catalase activity across all accessions under both stress conditions, with ILL7814 and ILL7835 recording the highest accumulations of 10.18 and 9.33 under drought stress, respectively, and 14 µmol H2O2 mg protein−1 min−1 under high temperature. Similarly, ascorbate peroxidase significantly increased in all tolerant accessions due to high temperatures, with ILL6359, ILL7835, and ILL8029 accumulating the highest values with up 50 µmol ascorbate mg protein−1 min−1. In contrast, no significant increase was obtained for all accessions subjected to water stress, although the drought-tolerant accessions accumulated more APX activity (16.59 t to 25.08 µmol ascorbate mg protein−1 min−1) than the sensitive accessions. The accessions ILL6075, ILL7814, and ILL8029 significantly had the highest superoxide dismutase activity under high temperature, while ILL6363, ILL7814, and ILL7835 accumulated the highest values under drought stress, each with 22 to 25 units mg protein−1. Under both stress conditions, ILL7814 and ILL7835 recorded the highest contents in proline (38 to 45 µmol proline/g FW), total flavonoids (0.22 to 0.77 mg QE g−1 FW), total phenolics (7.50 to 8.79 mg GAE g−1 FW), total tannins (5.07 to 20 µg CE g−1 FW), and total antioxidant activity (60 to 70%). Further, ILL7814 and ILL6338 significantly recorded the highest total soluble sugar content under high temperature (71.57 and 74.24 mg g−1, respectively), while ILL7835 achieved the maximum concentration (125 mg g−1) under drought stress. The accessions ILL8029, ILL6104, and ILL7814 had the highest values of reducing sugar under high temperature with 0.62 to 0.79 mg g−1, whereas ILL6075, ILL6363, and ILL6362 accumulated the highest levels of this component under drought stress with 0.54 to 0.66 mg g−1. Overall, our findings contribute to a deeper understanding of the metabolomic responses of lentil to drought and heat stresses, serving as a valuable reference for lentil stress tolerance breeding.